Analisa Pengaruh Kemampuan Kerja Pegawai Dan Komunikasi Antar Pribadi Terhadap Kualitas Pelayanan Perusahaan PT. Indosat tbk - M. Ifran Sanni; Sendy Zul Friandi; Danang Rifai (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2017)
Answering the challenges of the business world of telecommunications services with the sharpening of competition, Indosat need to do to improve the quality of service. For that we need a sober assessment of the factors that have an influence on the quality of the service itself. Suspected of employees working ability and interpersonal communication can affect the quality of service at the company experiment was conducted with the aim of proving allegations that an employee working ability and interpersonal communication together affect the quality of care in Indosat. From the results of data processing can be in the know that individually and the two independent variables have a relationshipand influence equally strong on the quality of service (r X1 = 0.621 and r x2 = 0.670) Collectively variable Job Skills Employees and Communication Between Personal Associated very strong with quality service on (R = 0.853) and by the coefficient of determination of 72.8% affect test results significantly with T test and F test proved significant at 95% confidence level, it can be concluded that: Alleged ability Employee Work and Inter-Personal Communication together effect on the quality of service at PT Indosat Tbk. Positive and significant effect can be received.